L-Methionine Protects against Oxidative Stress and Mitochondrial Dysfunction in an In Vitro Model of Parkinson's Disease - Mariano Catanesi; Laura Brandolini; Michele d'Angelo; Elisabetta Benedetti; Maria Grazia Tupone; Margherita Alfonsetti; Enrico Cabri; Daniela Iaconis; Maddalena Fratelli; Annamaria Cimini; Vanessa Castelli; Marcello Allegretti (MDPI AG, 2021)
Methionine is an aliphatic, sulfur-containing, essential amino acid that has been demonstrated to have crucial roles in metabolism, innate immunity, and activation of endogenous antioxidant enzymes, including methionine sulfoxide reductase A/B and the biosynthesis of glutathione to counteract oxidative stress. Still, methionine restriction avoids altered methionine/transmethylation metabolism, thus reducing DNA damage and possibly avoiding neurodegenerative processes. In this study, we wanted to study the preventive effects of methionine in counteracting 6-hydroxydopamine (6-OHDA)-induced injury. In particular, we analyzed the protective effects of the amino acid L-methionine in an in vitro model of Parkinson's disease and dissected the underlying mechanisms compared to the known antioxidant taurine to gain insights into the potential of methionine treatment in slowing the progression of the disease by maintaining mitochondrial functionality. In addition, to ascribe the effects of methionine on mitochondria and oxidative stress, methionine sulfoxide was used in place of methionine. The data obtained suggested that an L-methionine-enriched diet could be beneficial during aging to protect neurons from oxidative imbalance and mitochondrial dysfunction, thus preventing the progression of neurodegenerative processes.